HIV-I : molecular biology and pathogenesis : clinical applications - August, J. Thomas; Murad, Ferid; Jeang, Kuan-Teh. (Amsterdam ; Boston : Elsevier/Academic Press, 2008)
Although it is one of the most-widely studied viruses, many mysteries still remain about HIV. Covering the latest advances and challenges associated with clinical application of new antiviral drugs and vaccines, this revised edition is a companion to Murad:HIV-1: Molecular Biology and Pathogenesis, 2E. Leading investigators in HIV research present a timely picture of the molecular mechanisms which guide HIV-1 expression and replication and provide the most current clinical strategies for combating this virus. * The latest developments in HIV-vaccine research * New concepts in the discovery and design of novel anti-HIV drugs.
C. Inhibitors of the Initiation of Reverse TranscriptionD. RT-Directed Mutagenic Inducers; VII. Conclusion; Acknowledgments; References; A. Mechanism of Action of PIs; B. Protease Structures and Substrate-Based Inhibitors; C. Design of Symmetry-Based Inhibitors; D. Structure-Based PIs; A. Emergence of Drug Resistance to PIs; B. Primary and Secondary Mutations; C. Active site Mutants; D. Nonactive Site Mutants; E. Cleavage Site Mutants; F. Noncleavage Site Mutants; G. Insertions in Gag-Pol Polyproteins; VII. PIs with Activity Against Drug-Resistant HIV-1.
Previous edition: 2000.
Includes bibliographical references and index.
Print version record.
Text in English.
Elsevier
Keywords: HIV infections -- Molecular aspects; HIV infections -- Pathogenesis; HIV infections -- Treatment; AIDS vaccines; MEDICAL -- AIDS & HIV; HEALTH & FITNESS -- Diseases -- AIDS & HIV; AIDS vaccines; HIV infections -- Pathogenesis; HIV infections -- Treatment; Electronic books